Advances in activated carbon modification, surface heteroatom configuration, reactor strategies, and regeneration methods for enhanced wastewater treatment. Issue 4 (August 2021) - Lobato-Peralta, Diego Ramón; Duque-Brito, Estefanía; Ayala-Cortés, Alejandro; Arias, D.M.; Longoria, Adriana; Cuentas-Gallegos, Ana Karina; Sebastian, P.J.; Okoye, Patrick U.
Abstract: This review elucidates recent advances and challenges in the surface modifications of activated carbon (AC), the configuration of heteroatoms on activated carbon surface, and the mechanisms of their contributions as functional groups, reactor strategies, and regeneration of exhausted activated carbon for enhanced wastewater treatment. The studies found that different surface modification strategies change the surface chemistry of activated carbon, incorporate heteroatoms necessary to facilitate adsorption, and ozone treatment could increase surface acidity due to the production of carboxylic acids and lactone. Also, the modification methods by plasma and ozone seriously impact the pore size distribution and topography of ACs. Heteroatoms of sulphur, phosphorus, oxygen and nitrogen on the AC surface promote the adsorption of pollutants. Notable amongst the studied reactor strategies, microwave reactors present shorter activation time compared to other reactors. However, production in large volumes is still problematic with this type of reactor, and safety measures need to be strictly implemented to avoid radiation leaks. Although, regeneration of exhausted AC by thermal decomposition presents a facile and environmentally friendly route, however, this process adversely impacts the pore size distribution, surface area and often results in the loss of carbon materials. It is hoped that this study will provide detailed and recent knowledge on surface modifications of activated carbons, reactor strategies, and approaches to the regeneration of exhausted activated carbon. Graphical Abstract: ga1 Highlights: Surface functional groups can be tuned by different modification methods. Heteroatoms of S, O, N, and P promote adsorption of pollutants. Microwave reactors presents shortest activation time for AC production. Different regeneration methods impact AC textural properties.